TEACHERS' CHALLENGES AND STRATEGIES IN IMPLEMENTING ACTION DAY AT MUHAMMADIYAH 2 TULANGAN ELEMENTARY SCHOOL - Risha Agustina Widianata; Muhlasin Amrulloh (Proceeding International Symposium on Global Educatiorg Psychology, and Cultural Synergy, 2024)
Education in Indonesia faces great challenges in creating more effective and meaningful evaluation methods for students. Written exams are considered less capable of exploring students' potential as a whole. Various cheats were found from the implementation of written exams as an evaluation of student learning. In response to this challenge, SD Muhammadiyah 2 Tulangan implemented action day activities as a new breakthrough in learning outcomes evaluation innovation. The implementation of action day using the project-based learning (PjBL) learning model is considered effective in improving the ability to collaborate, think critically, and student creativity. However, the implementation faces a number of challenges, such as time constraints, lack of student enthusiasm, and difficulties in managing the class. This study aims to identify effective strategies to overcome these challenges and evaluate the success of Action Day implementation in improving learning quality. This research is expected to serve as a guideline for other schools in developing a more innovative evaluation system that has a positive impact on student learning.